Well-to-wheel carbon footprint and cost analysis of gasoline, diesel, hydrogen ICE, hybrid and fully electric city buses - Kuyumcu, Alen Murat; Bingul, Baris; Akar, Firat; Yildiz, Aleyna (PERGAMON-ELSEVIER SCIENCE LTD, 2024)
Carbon emissions in mobility, as one of the primary causes of global warming, are regulated by various organizations with different legislations. Different energy sources and power -train solutions are used to comply with these constraints. Hydrogen -fueled, fully electric, and hybrid vehicles are at the forefront of these technologies. Within the scope of this study, gasoline-, diesel-, and hydrogen -fueled internal combustion engines, and fully electric and serial hybrid 18-m city bus vehicles were modeled. Comprehensive analyses of emissions and costs, considering both the entire energy production and consumption cycles for various vehicle types were conducted. Models that are primarily based on fuel consumption data show that while fully electric vehicles currently have the lowest emissions, hydrogen -fueled vehicles can play a more prominent role soon with the increasing production of green hydrogen. For the first step of hydrogen implementation in the industry, H2ICE is a promising for both reduced carbon emissions in mobility and cost-effectiveness. If the forecasted hydrogen production and distribution scenario is adopted by industrial and energy organizations, it is evident that by the year 2030, more environmentally friendly operation can be achieved particularly in the context of public transportation. Embracing this approach is likely to lead to positive environmental sustainability impacts in future transportation systems.
Keywords: Carbon footprint; Hydrogen ICE; Fully electrical vehicle; Vehicle modeling; Well-to-Wheel; Cost analysis; EMISSIONS; Thermodynamics; Energy & Fuels